(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In Taiwan, the aging population has led to an increased demand for home-care workers. However, the turnover rate among Taiwanese home-care workers is relatively high. Therefore, it is critical to explore the possible factors that affect the turnover rate, including job satisfaction and psychological well-being which are important factors that affect the turnover of home-care workers. The objective of this study was to investigate the impact of personality on job satisfaction and psychological well-being. An observational cross-sectional study was designed to investigate this topic. We designed the questionnaire to collect the related data. The questionnaire included major characteristics of participants and three self-report measures, including personality, job stratification, and psychological well-being. Multiple regressions were adopted to investigate the relationship between personality and job satisfaction or psychological well-being. Our results demonstrated that openness was positively correlated with self-affirmation, while rigorousness was positively correlated with the internal factors of job satisfaction. Extraversion was positively correlated with the external factors of job satisfaction and life satisfaction, while agreeableness was positively correlated with life satisfaction. Neuroticism was positively correlated with the internal factors of job satisfaction, external factors of job satisfaction, self-affirmation, life satisfaction, and work achievement. After adjusting for confounding factors, openness was positively correlated with self-affirmation, and neuroticism was positively correlated with the internal factors of job satisfaction, external factors of job satisfaction, self-affirmation, life satisfaction, and work achievement. Our results suggest that the optimal home-care worker should possess specific personality traits, including a high level of openness and a low level of neuroticism.